Dear Mr. Henshaw - Cleary, Beverly; Juvenile Collection Library of Congress; Zelinsky, Paul O. (USA: Dell, 1984)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents$1 (Bdivorce, being the new boy in school, and generally finding his own place in the world.s
Keywords: Divorce -- Fiction; Imprints 20th century 1983; Juvenile literature -- New York (N.Y.)